2022
DOI: 10.1186/s12880-022-00954-8
|View full text |Cite
|
Sign up to set email alerts
|

Double contrast-enhanced ultrasound for the preoperative gross classification of gastric cancer: a comparison with multidetector computed tomography

Abstract: Purpose To compare the diagnostic performance of double contrast-enhanced ultrasound (DCEUS) and multi-detector row computed tomography (MDCT) in the gross classification of gastric cancer (GC) preoperatively. Methods 54 patients with histology proved GC were included in this retrospective study. The sensitivity and specificity of DCEUS and MDCT for the gross classification of GC was calculated and compared. The area under the curve (AUC) from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…With injection of 2.5 ml ultrasound contrast agent made from sulphur hexafluoride microbubbles, lesions can be assessed dynamically from the early arterial phase (10–15s) to the late phase (5 min), with no significant effects on thyroid function ( 8 ). Previous research has demonstrated that DCEUS can be a practical substitute for preoperative Borrmann classification of gastric cancer ( 9 ). In this particular case, DCEUS was utilized and successfully detected an SBA in the jejunum.…”
Section: Introductionmentioning
confidence: 99%
“…With injection of 2.5 ml ultrasound contrast agent made from sulphur hexafluoride microbubbles, lesions can be assessed dynamically from the early arterial phase (10–15s) to the late phase (5 min), with no significant effects on thyroid function ( 8 ). Previous research has demonstrated that DCEUS can be a practical substitute for preoperative Borrmann classification of gastric cancer ( 9 ). In this particular case, DCEUS was utilized and successfully detected an SBA in the jejunum.…”
Section: Introductionmentioning
confidence: 99%
“…With injection of 2.5 ml ultrasound contrast agent made from sulphur hexafluoride microbubbles, lesions can be assessed dynamically from the early arterial phase (10-15s) to the late phase (5 min), with no significant effects on thyroid function (8). Previous research has demonstrated that DCEUS can be a practical substitute for preoperative Borrmann classification of gastric cancer (9). In this particular case, DCEUS was utilized and successfully detected an SBA in the jejunum.…”
Section: Introductionmentioning
confidence: 91%